A Comprehensive Analysis of Electrolytes, Inϐlammatory Biomark‑ ers and Liver Function Enzymes Alterations in Hospitalized COVID‑ 19 Patients—Insights from a Single Center in Iraq - Omeed Darweesh; Marwah H. Mohammed (Trends in Immunotherapy, 2025)
Studying the status and involvement of laboratory biomarkers in COVID‑19 infection has the potential to enhance clinical management and improve the scenario in terms of morbidity and mortality. The aim of this study was to investigate the status of serum electrolytes, inflammatory biomarkers, and liver function enzymes, as well as their correlation with the severity of COVID‑19 infection. This observational study was conducted on 310 confirmed adult patients (> 18 years) with mild, moderate or severe symptoms of COVID‑19, admitted to Al‑Shifa 14 Hospital in Iraq between March and May 2022. The study outcomes were analyzed using one‑way ANOVA and Pearson’s correlation coefficient. Our data indicated that COVID‑19 patients with severe symptoms had notably lower levels of serum calcium (mmol/L) and potassium (mmol/L) compared to mild cases (calcium: 0.88 ± 0.04 vs. 1.13 ± 0.11; potassium: 3.03 ± 0.32 vs. 4.17 ± 0.46), respectively. In the severe group, both electrolytes were observed to be below normal levels. Inflammatory biomarkers, specifically C‑reactive protein and procalcitonin, demonstrated statistically significant elevations in severe cases compared to the moderate group, as well as in the moderate group compared to the mild group. Another significant finding was that liver function enzymes were notably elevated in patients with severe COVID‑19 compared to those with mild cases, as indicated by statistical analysis. Hypocalcemia, hypokalemia, and elevated liver function enzymes (ALP, AST, and bilirubin) were strongly associated with COVID‑19 severity. This research could provide a basis for using these biomarkers as useful assessment tools for COVID‑19 infections.